Dynamics between environmental taxes and ecological sustainability: Evidence from top‐seven green economies by novel quantile approaches. (7th October 2022) - Ullah, Sami; Luo, Rundong; Adebayo, Tomiwa Sunday; Kartal, Mustafa Tevfik
Abstract: Regulations and taxes are considered essential drivers for climate change policies and improving ecological quality. The prior research primarily relies on regulatory or non‐economic measures to ensure ecological sustainability, while the role of market‐based or economic measures in ecological sustainability is yet to be investigated. Hence, realizing the need for policy shift, this study is an effort to determine the dynamics between environmental taxes and ecological sustainability for the period between 1995/Q1 and 2018/Q4 using data of top‐seven green economies by employing novel Quantile‐on‐Quantile (QQ) regression approach. The outcomes from the QQ approach indicate the mixed and asymmetric impact of the environmental taxes on ecological sustainability in sample countries over different quantiles. However, a higher ecological promoting impact is observed at upper‐middle quantiles in most of the sample countries. The robustness of the study's results is validated by Quantile Regression (QR) approach and the nonparametric quantile causality test. The study's outcomes provide significant suggestions to formulate policies for helping sample economies to accomplish Sustainable Development Goals (SDGs) 7 and 13 while ensuring ecological sustainability.